Participatory communication in South African municipal government - Tshepang Bright Molale (Communicare)
The South African Municipal Systems Act (2000) directs South Africa’s municipalities to ensure that it uses IDP processes as a form of public participation in its affairs. This qualitative study was conducted in Jouberton Township in the Matlosana local municipality, North West Province, to assess the extent to which participatory communication takes place in municipal IDP processes. Using participant observation, semi-structured interviews and focus group discussions, the study found that community members were passive participators in municipal IDP processes in which their involvement was limited to being informed about what would happen or had already happened. Dialogue was facilitated through a top-down modernisation-based approach, and no evidence emerged of community empowerment in decision making regarding development projects. The findings suggest a need for the application of bottom-up participatory communication and “empowered” participation during municipal IDP processes. They also suggest a need for further research on how “participation as an end” can be theorised in line with participatory communication in a complex municipal system that already requires “participation as a means” to achieve certain goals.